KONSTITUSI PENDIDIKAN ISLAM DALAM MEMBANGUN MASYARAKAT MADANI - B, Abdullah (KURIOSITAS: Media Komunikasi Sosial Keagamaan, 2016)
This journal discuss how to Islamic education constituation in Indonesia and how are principles and implementation of islamic education in creating madani society.Islamic education constitution in indonesia be included in UU RI No 20 2003 it significant is developing ability and creating character it aims to develop students potential to be faithful and piety to god, good character, healthy, skillful, learned, creative, stand alone, and to be democratis citizen and responsible. Principles of Islamic education in building madani society are freely and individual freedom, freedom and individual activity must be balance and be control, free thingking and individual activity. Madani is an adoration value of fair, democrasy, freedom, prosperous.